IMPLEMENTASI METODE TEAM TEACHING PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM (PAI) DI SDN MARGAHAYU DESA PAPAYAN KECAMATAN JATIWARAS KABUPATEN TASIKMALAYA - Udin Zaenudin (Program Studi Pendidikan Agama Islam, 2022)
The purpose of this study was to find out the general description of PAI learning at SDN Margahayu; to find out the implementation of the Teaching Team method in PAI learning at SDN Margahayu; and to find out the evaluation system of the Teaching Team in PAI learning at SDN Margahayu, Papaya Village, Jatiwaras District, Tasikmalaya Regency. The results of this study indicate that in principle and in basic theory, the Team Teaching method at SDN Margahayu, Jatiwaras District, Tasikmalaya Regency is in accordance with the existing theoretical rules, the implementation (implementation) of the team teaching method in PAI learning at Margahayu Elementary School Jatiwaras District, Tasikmalaya Regency is carried out by two teachers, in carrying out this team learning, this second teacher jointly carries out lesson plans. Evaluation of the implementation of this Team Teaching, is by tests that are commonly carried out on all other subjects, namely in the form of giving good questions it is written or oral. Team Teaching evaluation is carried out by giving opening questions (pre-test) at the beginning of the implementation of Team Teaching (formative test), by carrying out daily evaluations to students, monthly evaluations, and summative evaluations.